2006
DOI: 10.1007/s11244-006-0014-9
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Exfoliated MoS2 in Hydrodesulfurization, Hydrodenitrogenation and Hydrogenation Reactions

Abstract: The activity of exfoliated MoS 2 in the hydrodesulfurization (HDS) of dibenzothiophene, the hydrodenitrogenation (HDN) of carbazole and the hydrogenation of naphthalene has been determined. The catalytic activity was compared to MoS 2 prepared by the decomposition of molybdenum naphthenate (MoNaph). Exfoliated MoS 2 was found to give better overall HDS activity compared to MoNaph derived MoS 2 catalyst, whereas MoNaph derived MoS 2 was found to give higher hydrogenation and HDN activity. These results are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
2
50
0
Order By: Relevance
“…Two-dimensional materials, such as molybdenum disulfide (MoS 2 ), have been extensively studied due to their applicability in different areas, such as catalysis, electrocatalysis, and electronic devices. [1][2][3][4][5][6][7][8] Furthermore, recent reports have demonstrated that 2D-MoS 2 has ahigh Young's modulus,for example, 270 GPa. [9][10][11][12][13] This impressive mechanical property associated with sheet morphology makes the 2D-MoS 2 acandidate for application asananofiller with polymericc omposites.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional materials, such as molybdenum disulfide (MoS 2 ), have been extensively studied due to their applicability in different areas, such as catalysis, electrocatalysis, and electronic devices. [1][2][3][4][5][6][7][8] Furthermore, recent reports have demonstrated that 2D-MoS 2 has ahigh Young's modulus,for example, 270 GPa. [9][10][11][12][13] This impressive mechanical property associated with sheet morphology makes the 2D-MoS 2 acandidate for application asananofiller with polymericc omposites.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on the HDS of model reactants to determine the kinetics of the reactions and this is a useful approach when quantifying the activity of different HDS catalysts . The reaction pathway for the HDS of DBT reported in these studies, presented in Figure , assumes two competing reaction steps for the HDS of DBT (direct desulphurization (DDS) that yields biphenyl (BP) and hydrogenation (HYD) that yields tetrahydrodibenzothiophene (THDBT)). Subsequent hydrogenation steps yield mostly cyclohexylbenzene (CHB) and bicylcohexyl (BCH) as well as minor amounts of other partially hydrogenated intermediates, such as cyclohexenylbenzene and hexahydrodibenzothiophene, that are dependent on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Atoms within a layer are bound by strong covalent forces, whereas individual layers are held together by van der Waals interactions. Although a large number of polytypes are observed for the transition metal chalcogenides, the most notable experimentally observed polytypes for MoS 2 and WS 2 based on the stacking sequence of the layers are a hexagonal polymorph with two layers in the unit cell, 2H (P63/mmc) symmetry; rhombohedral with three molecular layers in the unit cell, 3R (R3 m) symmetry; or the less common trigonal with one layer, 1 T. For instance, MoS 2 is a widely used compound with many applications in catalysis and as solid lubricants mainly because of the weak interlayer interaction of the material (Tye and Smith, 2004;Lince, 2004;Wu et al, 2010). More recent applications are hydrogen storage, as host-guest compounds, scanning tunneling microscope tips, and solid-state secondary lithium battery cathodes (Chen et al, 2001;Zak et al, 2002;Remskar et al, 2000;Homyonfer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%